TorsinA rescues ER-associated stress and locomotive defects in C. elegans models of ALS - Michelle L. Thompson; Pan Chen; Xiaohui Yan; Hanna Kim; Akeem R. Borom; Nathan B. Roberts; Kim A. Caldwell; Guy A. Caldwell (The Company of Biologists, 2014)
Molecular mechanisms underlying neurodegenerative diseases converge at the interface of pathways impacting cellular stress, protein homeostasis and aging. Targeting the intrinsic capacities of neuroprotective proteins to restore neuronal function and/or attenuate degeneration represents a potential means toward therapeutic intervention. The product of the human DYT1 gene, torsinA, is a member of the functionally diverse AAA+ family of proteins and exhibits robust molecular-chaperone-like activity, both in vitro and in vivo. Although mutations in DYT1 are associated with a rare form of heritable generalized dystonia, the native function of torsinA seems to be cytoprotective in maintaining the cellular threshold to endoplasmic reticulum (ER) stress. Here we explore the potential for torsinA to serve as a buffer to attenuate the cellular consequences of misfolded-protein stress as it pertains to the neurodegenerative disease amyotrophic lateral sclerosis (ALS). The selective vulnerability of motor neurons to degeneration in ALS mouse models harboring mutations in superoxide dismutase (SOD1) has been found to correlate with regional-specific ER stress in brains. Using Caenorhabditis elegans as a system to model ER stress, we generated transgenic nematodes overexpressing either wild-type or mutant human SOD1 to evaluate their relative impact on ER stress induction in vivo. These studies revealed a mutant-SOD1-specific increase in ER stress that was further exacerbated by changes in temperature, all of which was robustly attenuated by co-expression of torsinA. Moreover, through complementary behavioral analysis, torsinA was able to restore normal neuronal function in mutant G85R SOD1 animals. Furthermore, torsinA targeted mutant SOD1 for degradation via the proteasome, representing mechanistic insight on the activity that torsinA has on aggregate-prone proteins. These results expand our understanding of proteostatic mechanisms influencing neuronal dysfunction in ALS, while simultaneously highlighting the potential for torsinA as a novel target for therapeutic development.